2018
DOI: 10.1016/j.jesf.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The differences in physical activity levels in preschool children during free play recess and structured play recess

Abstract: Background/ObjectivePhysical activity (PA) is important in reducing childhood obesity, yet a majority of children are not meeting PA guidelines. Schools have been identified as a place to promote childhood PA. The purpose of this study was to determine the best type of physically active recess period to increase preschool-aged children's PA.MethodsPA was measured via accelerometers in preschool-aged children (n = 29) during three, 30-min recess conditions (control; structured play; free play) on separate schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 21 publications
1
20
1
15
Order By: Relevance
“…Non-formal learning is a learning mode and experience that takes place outside of conventional classrooms (Gilbertson, Bates, McLaughlin, & Ewert, 2006) that involves teachers in the process of learning with children. Whilst, informal learning is a motivated learning that happens without teachers' intervention during children's unstructured time, such as recess, and before and after school in the school grounds, which play is a central function (Frank, Flynn, Farnell, & Barkley, 2018). The children's play behaviour patterns were observed in terms of types of play and places where the activities occurred during both learning sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Non-formal learning is a learning mode and experience that takes place outside of conventional classrooms (Gilbertson, Bates, McLaughlin, & Ewert, 2006) that involves teachers in the process of learning with children. Whilst, informal learning is a motivated learning that happens without teachers' intervention during children's unstructured time, such as recess, and before and after school in the school grounds, which play is a central function (Frank, Flynn, Farnell, & Barkley, 2018). The children's play behaviour patterns were observed in terms of types of play and places where the activities occurred during both learning sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, children self-select their own activities daily, meaning that one day they may choose more sedentary activities, whereas another day, more active play 17. Studies have shown that children spend <50% of the time in PA during free-play periods, suggesting that adding structure to these periods may increase the amount of PA 12 50 51. The structure could involve providing equipment for children with instructions on how to use the equipment, or teachers’ prompts, encouragement or playing together with children 12 51.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children spend <50% of the time in PA during free-play periods, suggesting that adding structure to these periods may increase the amount of PA 12 50 51. The structure could involve providing equipment for children with instructions on how to use the equipment, or teachers’ prompts, encouragement or playing together with children 12 51. Interestingly, children with low levels of PA may benefit from this structured-type of free play, whereas the most active children often benefit more from having less structure 51.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of extrinsic motivation programs designed to maximize participation in physical activity in children is potentially important (Frank, Flynn, Farnell, & Barkley, 2018). Furthermore, according to Darden (1999), some of the benefits of visual educations in evaluation and teaching are; the student's motivation, interest and excitement may increase, helping to strive for learning, and can help to change the previously established negative behaviors in a positive way.…”
Section: Discussionmentioning
confidence: 99%